ANALYSIS OF MARKETING CHANNEL AND MARKETING MARGIN OF CATCHES OF KELONG SHRIMP AT TPI IN ALUE AMBANG VILLAGE, TEUNOM DISTRICT, ACEH JAYA DISTRICT - Shas Mitha Zein; Devi Agustia (CV. Radja Publika, 2023)
Marketing is considered efficient if it is able to convey results from producers to consumers and is able to make a fair distribution. The aim of the study was to determine the marketing channel and the amount of marketing margin by marketing agencies involved in shrimp marketing that occurred at TPI Alue Ambang Village, Teunom District, Aceh Jaya Regency. This research was conducted in Alue Ambang Village, Teunom District, Aceh Jaya Regency. There are two data used, namely primary data and secondary data. Data was collected from survey results with field observations. Snowball sampling sample method for a sample of fishermen with a total of 60 people. 7 collectors, 2 wholesalers. The results of this study are that there are two marketing channels that occur, namely from fishermen, then to collectors, then to wholesalers until it finally reaches consumers, and from fishermen, then to collectors, then to retailers until finally it reaches consumers. Meanwhile, the shrimp marketing margin at TPI Alue Ambang Village, Teunom District, Aceh Jaya Regency was IDR 45,000 in the first marketing channel. And IDR. 20,000 occurred in the second marketing channel.